2021
DOI: 10.1002/app.51360
|View full text |Cite
|
Sign up to set email alerts
|

Facile fabrication of diatomite‐based sponge with high biocompatibility and rapid hemostasis

Abstract: Excessive bleeding causes a large part of deaths in wars and accidents. It is necessary to prepare a hemostatic material with excellent performance and low cost through a facile strategy. Herein, the diatomite is modified with (3-Aminopropyl) triethoxysilane (APTES) to endow the aminated diatomite (ADia) with positive charge and interface compatibility with chitosan (CS) and sodium alginate (SA). Then, the facile fabrication of CS/SA/ADia sponge is successfully obtained by cross-linking with calcium ions. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…7,8 These properties have enabled its widespread utilization as a reinforcement filler, separation material, adsorbent precursor, and filtration agent. 9,10 Recent attention has been directed towards DIA as a flame retardant in polymer composites, owing to its remarkable thermal stability. In a study by Cavodeau et al, 11 the incorporation of DIA and aluminum hydroxide as co-fillers was shown to enhance the flame retardancy of ethylene-vinyl acetate composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 These properties have enabled its widespread utilization as a reinforcement filler, separation material, adsorbent precursor, and filtration agent. 9,10 Recent attention has been directed towards DIA as a flame retardant in polymer composites, owing to its remarkable thermal stability. In a study by Cavodeau et al, 11 the incorporation of DIA and aluminum hydroxide as co-fillers was shown to enhance the flame retardancy of ethylene-vinyl acetate composites.…”
Section: Introductionmentioning
confidence: 99%
“…Diatomite (DIA), a natural porous material originating from diatoms, is primarily composed of SiO 2 and boasts a high surface area, unique pore structure, non‐toxicity nature, and abundant availability 7,8 . These properties have enabled its widespread utilization as a reinforcement filler, separation material, adsorbent precursor, and filtration agent 9,10 . Recent attention has been directed towards DIA as a flame retardant in polymer composites, owing to its remarkable thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…The strength of the organic-inorganic interactions is relatively fragile in the microemulsion con ned space that makes it di cult to achieve a stable preparation process under high temperature conditions. In fact, it is di cult to obtain an economical and easy to handle large-scale synthesis method for zeolite particles in actual hemostatic emergency engineering [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%